Micro milling of fused silica using picosecond laser shaped single crystal diamond tools - Song, Jiacheng; Tong, Zhen; Yao, Zhenqiang; Jiang, Xiangqian (Frontiers in Materials, 2023)
Fused silica is widely used as a material for optical lenses owing to its excellent optical properties and low thermal expansion coefficient. However, as a hard and brittle material, there is very limited option of processing technologies to machining fused silica with surface structures. In this paper, a picosecond laser based single crystal diamond tool fabrication technology is proposed to generate micro milling tools with different geometrical designs, and the tool cutting performance is experimentally tested through micro-milling of fused silica under different cutting conditions. An optimal picosecond laser processing path is proposed to inhibit the graphitization of diamond tool and improve the concentricity of tool blades, and a multi-edge milling tool with a minimum rotary diameter of 0.4 mm can be obtained. The effects of rake angle on cutting force and the degree of brittle damage on the subsurface of fused silica are studied by micro milling tests of fused silica using the laser-shaped tools. The results show that the fused silica machined by diamond milling tool with a rake angle of -30° has the best surface finish (Ra = 41.2 nm). Using this laser-machined milling tool, a plurality of micro Fresnel lenses with aperture of 1.6 mm were successfully machined on a fused silica sheet.